2020
DOI: 10.1021/acs.estlett.0c00105
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Isotope Differences between Major Atmospheric NOy Species: Implications for Transformation and Deposition Processes

Abstract: Nitrogen isotopes (δ 15 N) can trace sources of major inorganic NO y species (here referring to nitrogen dioxide (NO 2 ), nitric acid (HNO 3 ), and nitrate (NO 3 − )) in the atmosphere. However, δ 15 N variations during transformation and deposition processes of NO y species remain poorly understood. Here, we dissected δ 15 N differences between NO 2 , HNO 3 , particulate NO 3 − , and precipitation NO 3 − by converging observations of their concentrations and δ 15 N from literature sources. δ 15 N values of HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 64 publications
1
10
0
Order By: Relevance
“…It is reported that non‐zero sea surface nitrite concentrations are required for RONO 2 formation to occur (Dahl & Saltzman, 2008; Dahl et al., 2012). Seawater nitrite concentrations along the cruise path were not measured in this study, but surface ocean nitrite has been reported to be approximately 0.5–2 μM in Region A (Chen et al., 2021; Hsieh et al., 2010; Liu, Ning, et al., 2020; Liu, Yin, and Song, 2020), 0.6–1.3 μM in Region B (Buchwald et al., 2015; Michoud et al., 2014; Mordy et al., 2010), and much lower in Region C (about 0.01–0.2 μM; Christman et al., 2011; Randall et al., 2012). Therefore, ocean RONO 2 emissions may be a non‐negligible source of atmospheric NO 3 − along the cruise path.…”
Section: Discussionmentioning
confidence: 77%
“…It is reported that non‐zero sea surface nitrite concentrations are required for RONO 2 formation to occur (Dahl & Saltzman, 2008; Dahl et al., 2012). Seawater nitrite concentrations along the cruise path were not measured in this study, but surface ocean nitrite has been reported to be approximately 0.5–2 μM in Region A (Chen et al., 2021; Hsieh et al., 2010; Liu, Ning, et al., 2020; Liu, Yin, and Song, 2020), 0.6–1.3 μM in Region B (Buchwald et al., 2015; Michoud et al., 2014; Mordy et al., 2010), and much lower in Region C (about 0.01–0.2 μM; Christman et al., 2011; Randall et al., 2012). Therefore, ocean RONO 2 emissions may be a non‐negligible source of atmospheric NO 3 − along the cruise path.…”
Section: Discussionmentioning
confidence: 77%
“…It has the potential to provide reliable estimations of source contributions because the isotope effect (i.e., 15 ∆ i-NO x →w-NO3− values in this study), the variability in δ 15 N values of both sources (i.e., δ 15 N values of NO x from S1–S4 in this study), and the mixture (i.e., δ 15 N w-NO3− values in this study) 45 , 46 are considered. The SIAR model has been widely used to quantify the relative contributions of multiple NO x emission sources to p-NO 3 − and w-NO 3 − 26 , 27 , 31 , 47 . In each run of the SIAR model, the mean ± SD of δ 15 N NO x values (Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…However, precipitation can scavenge both the ambient NO 2 and the oxidized NO 2 (i.e., HNO 3 and p-NO 3 − ) (Supplementary Fig. 1 ) 31 . Therefore, we can reconstruct the corresponding δ 15 N i-NO x values of the observed δ 15 N w-NO3− values (Supplementary Figs.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the Δ 17 O-O3* of 37.5‰ ± 2.2‰ was averaged from previous observations, corresponding to Δ 17 O-bulk O3 of 25‰ (Vicars et al, 2012;Vicars and Savarino, 2014). Our mean Δ 17 O-O3* of 37.5‰ was 2.8‰ higher and 1.5‰ lower than what was used in (Liu et al, 2020;Wang et al, 2019b) and (He et al, , 2020 for urban Beijing and Shanghai, respectively. When sensitivity test was conducted for the proportional contribution of the three oxidation pathways, a 2.8‰ change in Δ 17 O-O3* value caused 1.6‰, 2.1‰, and 2.5‰ change in the endmember for (1), (2), and (3) pathway, respectively.…”
Section: Contributions Of Major Hno3 Oxidation Pathwaysmentioning
confidence: 74%